The effects of taxes and bans on passive smoking - Jérôme Adda; Francesca Cornaglia (Centre for Microdata Methods and Practice (cemmap), 2005)
This paper evaluates the effect of excise taxes and bans on smoking in public places on the exposure to tobacco smoke of non-smokers. We use a novel way of quantifying passive smoking: we use data on cotinine concentration- a metabolite of nicotine- measured in a large population of non-smokers over time. Exploiting state and time variation across US states, we reach two important conclusions. First, excise taxes have a significant effect on passive smoking. Second, smoking bans have on average no effects on non smokers. While bans in public transportation or in schools decrease the exposure of non smokers, bans in recreational public places can in fact perversely increase their exposure by displacing smokers to private places where they contaminate non smokers, and in particular young children. Bans affect socioeconomic groups differently: we find that smoking bans increase the exposure of poorer individuals, while it decreases the exposure of richer individuals, leading to widening health disparities.
Keywords: 330; Gesundheitspolitik; Tabaksteuer; Rauchen; Soziale Schicht